Pancreas transplants. - Chandra, J; Phillips, R; Boardman, P; Gleeson, F; Anderson, E (2009)
Cadaveric, whole pancreas transplantation has proved an effective therapy in the treatment of long-standing type 1 diabetes mellitus and is capable of achieving an insulin-independent eugyclaemic state. As a result, this procedure is being increasingly performed. However, the surgical procedure is complex and unfamiliar to many radiologists. Imaging with computed tomography (CT) and magnetic resonance imaging (MRI) gives excellent results and can be used confidently to diagnose vascular, enteric, and immune-mediated complications. We present a review of the normal post-transplantation appearance and the features of early and late complications.